P09.17 Rectal infection with n. gonorrheae and c. trachomatis in men in the united states. (13th September 2015) - Tao, G; Hoover, K; Nye, M; Peters, P; Gift, T; Body, B
Abstract : Background: US guidelines recommend at least annual rectal chlamydia and gonorrhoea screening in men who have receptive anal intercourse. Data on rectal infection with chlamydia and gonorrhoea in men at the US national level are limited. Methods: In an ongoing collaboration with LabCorp, a large commercial laboratory corporation with a substantial share of the US market, we estimated rectal chlamydia and gonorrhoea positivity in male rectal specimens tested in 2014. Rectal specimens have unique test codes that are consistent among all LabCorp laboratories. LabCorp had previously validated rectal specimens in collaborative studies. Results: Of 38, 411 rectal specimens for chlamydia or gonorrhoea, 96.8% (37, 170) from 28, 945 men aged 15–60 years were tested for both chlamydia and gonorrhoea with nucleic acid amplification tests (NAAT). Of these men, 90.0% had private insurance and 5.0% had Medicaid; 15.4% were aged 15–24 years, 36.4% 25–34 years, and 22.5% 35–44 years. Of these 37, 170 specimens, 11.0% were positive for chlamydia, 8.3% gonorrhoea, and 2.4% both. Chlamydia and gonorrhoea positivity varied significantly (p < 0.01) by age (14.9% and 14.5% 15–24 years, 12.2% and 10.0% 25–34 years, 10.5% and 6.2% 35–44 years, and 7.7% and 4.2% >44 years, respectively). Of these specimens, 71.6% were collected by infectious disease doctors, 9.4% internists, 6.7% family doctors, and 2.6% public health providers. Conclusions: This study represents the largest analysis of rectal testing for chlamydial and gonococcal infection in the US Almost all men who receive rectal testing are tested for both chlamydia and gonorrhoea; most rectal testing is performed by infectious disease doctors. NAATs are not FDA cleared for rectal specimens, but many clinical laboratories have validated NAATs under CLIA guidelines and can perform rectal testing. The LabCorp dataset might be the best available source for estimating male rectal infection with chlamydia and gonorrhoea.